Integrated Agronursing Strategies to Mitigate Occupational Hazards among Global Agricultural Workers - Kurniyawan, Enggal Hadi; Afandi, Alfid Tri; Nur, Kholid Rosyidi Muhammad; Kurniawan, Dicky Endrian; Mahardhika Rahmawati, Primasari; Emerson, Iraha; Mukhtar, Madiha; Rany Agustin Wulandari (Health and Technology Journal (HTechJ), 2026)
Agricultural occupational hazards pose escalating threats to farming populations globally, yet fragmented evidence limits cohesive clinical and policy responses. This systematic review synthesizes contemporary research to inform an integrated agronursing framework addressing occupational health and safety among farmers. Following PRISMA 2020 guidelines, we searched Scopus, PubMed, and ProQuest for English-language, open-access studies published between 2022 and 2026. Ten studies spanning eight countries underwent a Joanna Briggs Institute critical appraisal and narrative synthesis due to methodological heterogeneity. Results indicate strong positive correlations between hazard knowledge and safety behaviors, though high-risk practices persist, including pesticide overconcentration (74.6%) and inconsistent use of personal protective equipment. Panel regression analysis revealed a monotonic escalation in severe agricultural trauma above 20°C, increasing 123% beyond 30°C. Multicomponent educational interventions demonstrated significant short-term improvements in sun safety knowledge and protective behaviors. At the same time, qualitative evidence highlighted structural determinants, piece-rate compensation, infrastructure deficits, and cultural norms that independently mediate risk exposure. Media analyses further revealed tendencies to individualize injury responsibility, obscuring upstream regulatory drivers. These findings confirm that knowledge acquisition alone cannot sustain behavioral change without concurrent environmental and policy-level interventions. Consequently, agronursing practice must evolve from episodic clinical care toward proactive, ecologically grounded models integrating standardized psychosocial screening, climate-responsive surveillance, and advocacy for equitable safety protocols. This framework equips rural health systems with evidence-based strategies to implement contextually tailored interventions, ultimately safeguarding farmer wellbeing and strengthening global agricultural resilience.